Robotic-assisted versus conventional hip arthroplasty: a comparative analysis of perioperative blood management and early outcomes - Annapareddy Adarsh; Jayakumar Tarun; Reddy Manideep; Mulpur Praharsha; Gurram Vijay Kumar Reddy; Prasad Vemaganti Badri Narayana; Gurava Reddy A. V. (SICOT-J)
Purpose: This study aimed to evaluate the impact of Robotic-Assisted Total Hip Arthroplasty (RATHA) versus Conventional Total Hip Arthroplasty (CTHA) on perioperative blood loss, blood transfusion requirements, and early clinical outcomes. Methods: A prospective cohort study was conducted at a high-volume tertiary care center from January 2021 to January 2023. A total of 200 patients undergoing primary THA were equally divided into RATHA (using the MAKO SmartRobotics system) and CTHA cohorts. Propensity score matching adjusted for demographics and baseline characteristics, resulting in 172 matched patients. Primary outcomes included changes in perioperative hemoglobin, estimated blood loss (EBL), and transfusion rates. Secondary outcomes assessed were operative time, length of stay, and transfusion-related adverse events. Results: The RATHA group demonstrated significantly lower post-operative hemoglobin drops (2.49 ± 0.6 g/dL vs. 3.38 ± 1.0 g/dL; p < 0.001), reduced EBL on post-operative day 3 (1125.52 ± 361.2 mL vs. 1611.12 ± 501.4 mL; p < 0.0001), and lower transfusion rates (7.96% vs. 20.4%; p = 0.0175) compared to the CTHA group. Operative time was significantly shorter in the RATHA group (68.01 ± 8.7 minutes vs. 77.1 ± 10.5 minutes; p < 0.0001). All robotic cohort patients were discharged within 3 days, whereas 14% of CTHA patients required extended hospitalization. Conclusion: This study demonstrates that robotic-assisted total hip arthroplasty (RATHA) significantly reduces perioperative blood loss, hemoglobin drop, and blood transfusion rates compared to conventional total hip arthroplasty (CTHA). The observed decrease in operative time and hospital stay in the RATHA group further suggests that robotic assistance may enhance procedural efficiency and support faster patient recovery.